2005
DOI: 10.1093/humrep/deh725
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant intake is associated with semen quality in healthy men

Abstract: In a convenience sample of healthy non-smoking men from a non-clinical setting, higher antioxidant intake was associated with higher sperm numbers and motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
157
2
15

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(186 citation statements)
references
References 29 publications
12
157
2
15
Order By: Relevance
“…In Eskenazi's study vitamins C, E and beta-carotene were associated with semen quality in 97 healthy non-smoking men. They revealed that a high intake of antioxidants is associated with better sperm quality [56].…”
Section: Discussionmentioning
confidence: 99%
“…In Eskenazi's study vitamins C, E and beta-carotene were associated with semen quality in 97 healthy non-smoking men. They revealed that a high intake of antioxidants is associated with better sperm quality [56].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the latest data released by the Society for Assisted Reproductive Technology (SART, www.sart.org), corresponding to IVF patients in 2011, the incidence of male factor was: male factor (17 %), mixed male and female factor (18 %), other factors (8 %) and unknown factors (12 %). The aetiology of diminished semen quality is poorly understood, although both environmental and occupational factors, as well as lifestyle, have been implicated [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Eighty seven men with decreased sperm motility (asthenozoospermia) received Vitamin E (100 mg 3 times daily) for 6 months had significantly decreased levels of lipid peroxidation product and improved sperm motility as compared to the placebo group [49]. Higher levels of Vitamin E intake were associated with higher levels of progressive sperm motility [50].…”
Section: Resultsmentioning
confidence: 99%